Desenvolvimento regional e políticas territoriais : estruturas produtivas regionais no Pantanal brasileiro - Lima, Diogo Marcelo Delben Ferreira de (2012)
This paper analyzes the regional development of the Brazilian Pantanal from territorial policies and their effect on the productive structures of the sugar cane and cattle, these important economic activities in the region and established in the territory preterit. The work is critical and is supported approach with the techniques of social research. The category region is developed as theoreticalmethodological support for geographic analysis, but not as a product space determined by social and environmental attributes, but as an expedient that allows academic and scientific discussion of socio-spatial issues. Another band, the territorial dimension expressed by the relations of power and ownership of natural resources is contemplated for a better understanding of severe environmental degradation and worsening of social dilemmas. Therefore, total territorial policies seeking not only to prevent abuse of economic power, but to ensure minimum legal standards for the conservation of natural resources and respect the rights of people, but that does not cease to be associated with particular interests in various scales. This time, the Brazilian Pantanal region, inserted into the country, consists of the territory subject to the prohibitions macropoderes instituted policies that have hampered regional development, in particular, the performance of regional productive structures of the sugar cane and livestock bovine.